2016
DOI: 10.1021/acs.bioconjchem.6b00040
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a Ligand-Dependent Enzyme by Fusing Circularly Permuted Antibody Variable Region Domains

Abstract: Allosteric control of enzyme activity with exogenous substances has been hard to achieve, especially using antibody domains that potentially allow control by any antigens of choice. Here, in order to attain this goal, we developed a novel antibody variable region format introduced with circular permutations, called Clampbody. The two variable-region domains of the antibone Gla protein (BGP) antibody were each circularly permutated to have novel termini at the loops near their domain interface. Through their at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Therefore, it is important to mention that the size of the inserted protein has only little impact on the resulting chimeric protein. Indeed, it has been shown that large structured domains can be successfully inserted into β-lactamases, as long as their Nand C-terminal extremities are flexible or close to each other 13,14,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29 . In the present study, the insertion site in BlaP is located far away from its active site and the inserted nanobody has relatively long and flexible extremities (not visible in the X-ray structure) that are located far away from the paratope.…”
Section: Limitations Of the Hybrid β-Lactamase Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is important to mention that the size of the inserted protein has only little impact on the resulting chimeric protein. Indeed, it has been shown that large structured domains can be successfully inserted into β-lactamases, as long as their Nand C-terminal extremities are flexible or close to each other 13,14,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29 . In the present study, the insertion site in BlaP is located far away from its active site and the inserted nanobody has relatively long and flexible extremities (not visible in the X-ray structure) that are located far away from the paratope.…”
Section: Limitations Of the Hybrid β-Lactamase Technologymentioning
confidence: 99%
“…Indeed, the presence of a flexible linker (e.g. Gly-Ser repetitions) to connect the carrier and the inserted protein was shown to dramatically increase the tolerance towards the insertion of large and structured proteins into a carrier one 30,12 .…”
Section: Limitations Of the Hybrid β-Lactamase Technologymentioning
confidence: 99%
See 1 more Smart Citation